Efficacy of Combining An Inferior Alveolar Nerve Block with A Buccal Infiltration For Mandibular Molars with Irreversible Pulpitis-A Randomized Controlled Study - Abbas, Mehvish; Ahmed, Ayesha; Rasheed, Dil; Rana, Muzammil Jamil; Ramzan, Iram (Pakistan Armed Forces Medical Journal, 2025)
Objective: To compare the effectiveness of a combined technique using an inferior alveolar nerve (IAN) block and buccal infiltration versus an IAN block alone in performing endodontic treatment on mandibular molars with irreversible pulpitis.Study Design: Randomized clinical trial (ClinicalTrials.gov: NCT06276842).Place and Duration of Study: Department of Operative Dentistry, Armed Forces Institute of Dentistry Rawalpindi, Pakistan from Apr-Sep 2020.Methodology: There were 120 participants participating in this study. The study participants were divided into 2 groups, Group-A included sixty patients who received conventional IAN block, and sixty patients of Group-B received buccal infiltration along with conventional IAN block.Results: Median age of the patients is 31.50 (37.00-23.25) years. There were 72(60%) male and 48(40%) female patients. Effectiveness of anesthesia in Group-B was statistically (p-value < 0.05) significant than Group-A.Conclusion: The combination of IAN block with buccal infiltration as a supplementary anesthesia technique has significant effect in controlling pain among patients suffering from irreversible pulpitis of lower molar as compared to conventional IAN block technique alone.